Hepatocyte‐specific eNOS deletion impairs exercise‐induced adaptations in hepatic mitochondrial function and autophagy. Issue 5 (31st March 2022) - Cunningham, Rory P.; Moore, Mary P.; Dashek, Ryan J.; Meers, Grace M.; Jepkemoi, Vivien; Takahashi, Takamune; Vieira‐Potter, Victoria J.; Kanaley, Jill A.; Booth, Frank W.; Rector, R. Scott
Abstract: Objective: Endothelial nitric oxide synthase (eNOS) is a potential mediator of exercise‐induced hepatic mitochondrial adaptations. Methods: Here, male and female hepatocyte‐specific eNOS knockout (eNOS hep−/− ) and intact hepatic eNOS (eNOS fl/fl ) mice performed voluntary wheel‐running exercise (EX) or remained in sedentary cage conditions for 10 weeks. Results: EX resolved the exacerbated hepatic steatosis in eNOS hep−/− male mice. Elevated hydrogen peroxide emission (~50% higher in eNOS hep−/− vs. eNOS fl/fl mice) was completely ablated with EX. Interestingly, EX increased [1‐ 14 C] palmitate oxidation in eNOS fl/fl male mice, but this was blunted in the eNOS hep−/− male mice. eNOS hep−/− mice had lower markers of the energy sensors AMP‐activated protein kinase (AMPK)/phospho‐ (p)AMPK and mammalian target of rapamycin (mTOR) and p‐mTOR, as well as the autophagy initiators serine/threonine‐protein kinase ULK1 and pULK1, compared with eNOS fl/fl mice. Females showed elevated electron transport chain protein content and markers of mitochondrial biogenesis (transcription factor A, mitochondrial, peroxisome proliferator‐activated receptor‐gamma coactivator 1α). Conclusions: Collectively, this study demonstrates for the first time, to the authors' knowledge, the requirement of eNOS in hepatocytes in the EX‐induced increases in hepatic fatty acid oxidation in male mice. Deletion of eNOS in hepatocytes also appears to impair the energy‐sensing ability of the cell and inhibit the activation of the autophagy initiating factor ULK1. These data uncover the important and novel role of hepatocyte eNOS in EX‐induced hepatic mitochondrial adaptations.